(untitled) (International Association of Biologicals and Computational Digest, 2022)
sulfur (S), also spelled sulphur, nonmetallic chemical element belonging to the oxygen group (Group 16 [VIa] of the periodic table), one of the most reactive of the elements.Sulfur is classified among the minor constituents of Earth’s crust, in which its proportion is estimated to be between 0.03 and 0.06 percent. Coal is classified into four main types, or ranks: anthracite, bituminous, subbituminous, and lignite. Geochemical studies of sulfur in coals comprise several major aspects relating to the nature and origin of sulfur in coals, including the abundance and distribution of sulfur in coal seams, abundance of sulfur in coal lithotypes and macerals (Chen-Lin Chou, 2012). All types of coal also contain sulfur, which, when burned, releases toxic air pollution. Sulfur content is determined by the conditions under which the coal is formed. While Petroleum coke is a byproduct of petroleum refining, useful in the production of may things.